Psychological resilience and competitive anxiety among professional athletes during high stakes international tournaments - Andi Wijaya; Robert J Miller; Hiroshi Tanaka (Gorontalo State University, 2026)
The psychological demands of international competition are immense, yet there is a lack of comprehensive research investigating the specific interaction between trait resilience and state anxiety during high-stakes events. While physical skills are often equalized at the elite level, the mental mechanisms that determine success remain under-explored. This study aims to investigate how psychological resilience mediates competitive anxiety and affects overall performance outcomes. Employing a mixed-methods approach, the researchers analyzed data from 250 elite athletes across multiple disciplines using the Connor-Davidson Resilience Scale and physiological stress markers. The findings reveal a significant inverse correlation between resilience levels and cognitive anxiety, suggesting that high-resilience athletes maintain superior executive function under pressure. This research introduces a novel